Clinical Outcomes of Magnesium-Based Balloon-Expandable Biodegradable Stenting for Benign Biliary Strictures: A Single-Center Retrospective Cohort Study - Mariano Eduardo Giménez; Chiara Innocenzi; Ignacio Corteggiano; Juliana Maria Racedo; Lucas Fehlauer; Samantha Robert; Pablo Acquafresca; Eduardo Houghton; Mariano Palermo (Journal of Laparoendoscopic & Advanced Surgical Techniques, 2026)
Background: Benign biliary strictures, most commonly anastomotic after hepaticojejunostomy or related to bile duct injury, are conventionally managed with balloon dilation, multiple plastic stents, or covered metal stents, all of which typically require repeated procedures. Magnesium-based balloon-expandable biodegradable stents (UNITY-B) have been proposed as a single-step alternative, but dedicated cohort data are limited. Methods: We retrospectively reviewed 22 consecutive UNITY-B stent-placement procedures performed in 21 patients with benign biliary strictures at a single center (April 2024–February 2026). The primary endpoint, clinical success (freedom from stricture recurrence during follow-up), was estimated using the Kaplan-Meier method at the patient level ( n = 21), with a procedure-level sensitivity analysis ( n = 22) and a competing-risks sensitivity analysis (Aalen-Johansen estimator) accounting for two unrelated deaths. Technical success and stent-related complications, assessed within 30 days after stent placement, were evaluated at the procedure level. Results: Median age was 58.0 years (interquartile range 51.0–70.0); 76.2% of strictures were anastomotic at a hepaticojejunostomy. Technical success was achieved in 22/22 procedures (100%), with no stent-related complications within 30 days. Stricture recurrence occurred in 6/21 patients (28.6%) at a median of 7.0 months; all underwent reintervention. Kaplan–Meier freedom from recurrence was 90.5% (95% CI 67.0–97.5%) at 6 months and 66.0% (95% CI 38.7–83.3%) at 12 months. Two deaths, unrelated to the procedure, occurred during follow-up. Conclusions: In this small, retrospective, single-arm cohort, magnesium-based balloon-expandable biodegradable biliary stenting was technically feasible, with no stent-related complications observed within 30 days after stent placement, and freedom from recurrence in approximately two-thirds of patients at 1 year. These findings are hypothesis-generating; prospective comparative studies with longer follow-up are needed before this approach can be positioned relative to established alternatives.